Robotic transanal total mesorectal excision assisted by laparoscopic transabdominal approach: A preliminary twenty-case series report - Je-Ming Hu (Asian Journal of Surgery, 2020)
Summary: Background: Laparoscopy-assisted robotic transanal total mesorectal excision is a novel surgical technique for rectal cancer resection. Compared to prior DaVinci Si system case series, this case series is the first to report robotic taTME assisted by laparoscopy (r-taTME) in which the “transanal team” operates via the DaVinci Xi system. As a result, we aim to delineate and discuss preliminary findings from our robotic taTME experiences. Methods: A total of twenty patients (twelve males) who underwent robotic taTME assisted by laparoscopy (r-taTME) between January 2016 and November 2016 at a single institution were documented. Surgical outcomes, including complications, pathological outcomes, and short-term results, were then retrospectively analyzed. Results: All patients underwent r-taTME via a two-team approach. The “abdominal team” operated via a single port method (ileostomy site), while the “transanal team” operated via the DaVinci Xi system. The mean patient age was 56.7 ± 14.3 years (range 31–79), and the mean distance from tumor to anal verge was 6.0 ± 2.7 cm (range 2–10). The mean estimated intraoperative blood loss was 88 ± 107 ml (range 30–500), and circular stapling was utilized to restore continuity in 80% of study patients. The overall postoperative complication rate was 35%, and the mean distal margin length was 3.1 ± 1.3 cm. There were three patients who had a circumferential margin (CRM) involved by cancer cells (≤1 mm). Conclusion: Our preliminary series report demonstrates that utilization of r-taTME assisted by laparoscopy is safe and feasible. Development of a novel transanal approach that allows single-port access alongside a multi-arm robotic system may increase the convenience and efficiency of future operation. Keywords: Robotic surgery, Robotic taTME, Rectal cancer, Transanal TME, DaVinci Xi